2018
DOI: 10.2174/1570159x15666171017102547
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Dietary Fats on Brain Functions

Abstract: Despite the knowledge of the molecular mechanisms is still a work in progress, the clinical relevance of the manipulation of dietary fats is well acknowledged and such manipulations are in fact currently in use for the treatment of brain diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
95
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 115 publications
(100 citation statements)
references
References 331 publications
(327 reference statements)
0
95
0
5
Order By: Relevance
“…The consumption of HFD lowers the expression of tight junctions in the intestinal epithelium, which has been associated with subsequent obesity, insulin resistance, and hyperglycemia in both human and animal models [1,2]. HFD could also adversely affect the brain by impairing cognitive functions or promoting depression-like symptoms [3][4][5]. Several animal studies have demonstrated that dietary shifts from HFD to a balanced diet could correct adverse effects resulted from HFD with permanent or transgenerational bene ts [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…The consumption of HFD lowers the expression of tight junctions in the intestinal epithelium, which has been associated with subsequent obesity, insulin resistance, and hyperglycemia in both human and animal models [1,2]. HFD could also adversely affect the brain by impairing cognitive functions or promoting depression-like symptoms [3][4][5]. Several animal studies have demonstrated that dietary shifts from HFD to a balanced diet could correct adverse effects resulted from HFD with permanent or transgenerational bene ts [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Excessive intake of fat in diets negatively affects brain and cardiovascular functions, and the metabolic disorders related to cerebral and cardiovascular systems are strongly correlated with mitochondrial dysfunction, responsible for the development of ischemic diseases in these tissues [ 6 , 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Within the context of specific dietary nutrients as determinants of the alterations of microbial communities and increased liability to NPDs, a special attention should be focused on a particular class of lipids derived from microbial metabolism and made of SCFAs. The processing of dietary nutrients by microbial metabolism generates a complex signaling system principally composed of SCFAs, L-tryptophan (Trp) metabolites and neuroactive agents [47,153,154]. Trp metabolism and neuroactive agents are also of key importance for the understanding of the relationship between MBC and risk of NPDs.…”
Section: Short Chain Fatty Acids and Microbiota Community: Implicatiomentioning
confidence: 99%